Live experience of people with diabetes mellitus on selfmanagement during COVID-19 in remote area of Indonesia - Eka, Angelina Roida; Mariati, Lusia Henny; Simon, Maria Getrida; Dewi, Claudia Fariday; Iwa, Kornelia Romana; Demang, Fransiska Yuniati; Hepilita, Yohana; Krowa, Yuliana Reginaldis Rosali (Gaceta Médica de Caracas, 2022)
Introduction: People with Diabetes Mellitus (DM) are vulnerable to COVID-19. Therefore, it’s important to maintain good self-management (diet, exercise, medicine, and health care visitations) during pandemics. Unfortunately, during the COVID-19 pandemic, it’s difficult for them to maintain adequate self-management. Therefore, this study aimed to explore the self-management of people with DM during the pandemic, especially in a remote area of Indonesia.